Promise, Provision, and Potential: A Hopeful Trajectory for Spiritual Care in Long-Term Care - Kuepfer, Jane (Journal of pastoral care & counseling, 2022)
This Canadian study aimed to better understand the provision of spiritual care in long-term care homes, its purpose/importance, the role of a spiritual care provider (SCP)/chaplain, effective practices, and challenges. Online survey responses revealed the need for spiritual care and the robust role of SCPs. Recommendations are made for more consistent employ and integration of SCPs, supported by sector-specific training and a system to connect LTC homes with skilled SCPs.